Emerging tyrosine kinase inhibitors for the treatment of metastatic colorectal cancer. (2nd July 2016) - Matos, Ignacio; Elez, Elena; Capdevila, Jaume; Tabernero, Josep
ABSTRACT: Introduction : Colorectal cancer (CRC) is a leading cause of cancer death worldwide. Over the last decade, the addition of antibodies that block the epidermal growth factor receptor (EGFR) or angiogenesis to the classic chemotherapy backbone has improved overall survival in metastatic colorectal cancer (mCRC). However, the role of the other major targeted therapy, the tyrosine kinase inhibitors (TKIs), is not yet fully clarified. Areas covered : This review discusses key published and ongoing studies with TKIs in mCRC, the mechanisms of resistance to standard treatments that are potentially targetable with these small molecules, along with the role of biomarkers in therapeutic decision-making process. Expert opinion : The current effectiveness of TKIs is limited by two principal reasons, firstly the use of combination chemotherapy necessitates lower dose-density to manage the toxicity profile and secondly, development of these drugs has mainly been performed in molecularly unselected populations. mCRC is a heterogeneous and dynamic disease, and clinical trials with TKIs must be designed on the basis of specific molecular alterations targeted by these drugs. Success with this approach relies on identifying mutations at the time of progression, raising the importance of minimally-invasive monitoring tools. Liquid biopsies are a promising option, although this technique remains to be validated. Overall, this approach contributes to the move towards personalized and precision therapeutic strategies.